Temporalità sovrapposte. Articolazione del tempo e costruzione della presenza nei media immersivi - Eugeni, Ruggero (Scenari, 2021)
This article analyze the concept of “presence” in different areas, technical and philosophical, with reference to immersive experiences offered by virtual reality’s recent applications. According to this exam, this article claims that (a) there are different degrees and configurations of the subject’s presence compared to virtual world; (b) these configurations was already partly esplored by cinema and (c) especially in the case of relate virtual they depend on the temporal (more than spatial) structures of the experience arranged to the subject.